2019
DOI: 10.1111/hae.13774
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilia Experiences, Results and Opportunities (HERO study) in Brazil: Assessment of the psychosocial effects of haemophilia in patients and caregivers

Abstract: Introduction The international Haemophilia Experiences, Results and Opportunities (HERO) study assessed the psychosocial aspects of life for people with haemophilia (PWH) and their caregivers in several countries. Brazil was not included in this initiative. Aim and methods An observational, multicentre, cross‐sectional study was performed involving PWH (moderate‐to‐severe haemophilia) and their caregivers, from November 2014 to July 2015. The primary objective was to quantify the extent of the primary psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
(70 reference statements)
2
13
0
Order By: Relevance
“…[1][2][3][4][5][6][7] In high-income countries, such as United States and Europe, this information has been collected mainly through surveys involving healthcare professionals, with fewer surveys involving also patients and caregivers. [1][2][3][4][5][6][7] The lack of robust and multifaceted researches that explore and quantify the healthcare, social and psychological aspects of PWH, has led to the development of international initiatives to collect information reported by health care professionals, patients and caregivers. However, also, these important surveys were conducted in a period, between 2011 and 2015, that do not represent the current changing scenario of haemophilia treatment and management and the relative impact on patients' lives.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In high-income countries, such as United States and Europe, this information has been collected mainly through surveys involving healthcare professionals, with fewer surveys involving also patients and caregivers. [1][2][3][4][5][6][7] The lack of robust and multifaceted researches that explore and quantify the healthcare, social and psychological aspects of PWH, has led to the development of international initiatives to collect information reported by health care professionals, patients and caregivers. However, also, these important surveys were conducted in a period, between 2011 and 2015, that do not represent the current changing scenario of haemophilia treatment and management and the relative impact on patients' lives.…”
Section: Introductionmentioning
confidence: 99%
“…The daily challenges faced by people with hemophilia and their caregivers can have a significant negative impact on well-being, as well as psychosocial functional status. 24 The Haemophilia Experiences, Results and Opportunities (HERO) study in North America reported severe pain interference in approximately 30% of PwH aged >30 years, 25 while results from the HERO survey in Brazil revealed that 64% of adult male PwH have moderate/ severe pain, 26 both based on analysis of the standardized EuroQOL five dimensions questionnaire (EQ-5D). Analysis by O'Hara et al of young adults (aged 18-35 years) treated with primary prophylaxis in the CHESS survey, showed that 73% of respondents had at least one bleed event in past 12 months.…”
mentioning
confidence: 99%
“…Several study limitations should be considered when interpreting the results. First, the survey questionnaire used was designed for the purposes of the study but was not subjected to rigorous psychometric and clinimetric testing; in contrast, the HERO 25,26 and CHESS studies 27 both used the standardized EQ-5D domain analysis. Items for our questionnaire were based on expert opinion as well as from the literature but did not include any standardized assessment of the validity, reliability and responsiveness of the questionnaire.…”
mentioning
confidence: 99%
“…Increased factor costs associated with prevention could be balanced by avoiding direct and indirect costs of managing bleeding episodes and complications [58,59]. The non-economic benefit of this approach would be improved quality of life for patients along with their caregivers and families [60,61]. Compliance with factor replacement regimens must be optimized as well to fully actualize these expected benefits.…”
Section: Discussionmentioning
confidence: 99%